Perilaku Pemilih Pemula Masyarakat Kecamatan Leuwiliang Kabupaten Bogor Pada Pemilihan Umum Tahun 2024 - Chikal Akmalul Fauzi; Djoni Gunanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study aims to conduct an analysis of the factors that form the basis for all Indonesian people who have just participated in the general election in Leuwiliang District in 2024. A total of 10,344 people in Leuwiliang District are people who have just held general elections and have used their voting rights for the first time in 2024 from a total of 11,959 people on the Permanent Voters List (DPT). Based on these data, there are still 1,615 people who are voting for the first time in Leuwiliang District who did not come to the Polling Station (TPS) to exercise their right to vote, which is certainly influenced by several factors or certain reasons, such as not knowing the candidates who will be elected in executive and legislative positions and the entire vision and mission of each candidate. The method in this study uses a qualitative method with data collection techniques, namely interviews and document studies. The results of this study are that 64% of new voters who came to the polling stations to 'vote' chose based on the social approach model and 35% based on the rational approach model.